HLA‐A*24:386, a novel variant of HLA‐A*24, discovered in a Taiwanese blood donor. (21st September 2018) - Yang, K. L.; Lin, P. Y.
Abstract : One nucleotide replacement at residue 181 of HLA‐A*24:02:01:01 results in a novel allele, HLA‐A*24:386.